Rhodococcus aromaticivorans sp. nov., an o-xylene degrading bacterium, and evidence supporting reclassification of Rhodococcus jostii RHA1 - Neak Muhammad; Jehyun Jeon; Eungbin Kim; Dockyu Kim; Yung Mi Lee (PLoS ONE, 2025)
A Gram-positive, aerobic, non-motile bacterium with a rod-coccus shape, designated DK17 T , was isolated from a crude oil-contaminated soil and identified as a member of the genus Rhodococcus based on 16S rRNA gene analysis, showing highest similarity (99.93%) to Rhodococcus jostii DSM 44719 T . However, average nucleotide identity (ANI) and digital DNA-DNA hybridization (dDDH) values between strain DK17 T and type strains within the genus Rhodococcus were below the species delineation thresholds of 95% and 70%, respectively. In contrast, DK17ᵀ exhibited ANI and dDDH values over 99% and 92%, respectively, with R. jostii RHA1. Comparative genomic analysis revealed that DK17 T and RHA1 shared 93.5% of genes, while RHA1 and R . jostii NBRC 16295 T shared only 78.6%, indicating a closer relationship between DK17 T and RHA1. Both strains possess large genomes (~9.5–9.7 Mb) comprising a linear chromosome and multiple plasmids, and encode multiple dioxygenases and secondary metabolite biosynthetic gene clusters. In vitro assays confirmed o -xylene degradation by both DK17 T and R. jostii RHA1, consistent with the presence of the akb gene cluster. Both strains shared C 16:0 as a major fatty acid and menaquinone-8 (H2) as the dominant quinone. Based on genomic, phenotypic, and chemotaxonomic data, DK17 T (=KCCM 90599 T = InaCC B1662 T ) is proposed as a novel species, Rhodococcus aromaticivorans sp. nov., and R. jostii RHA1 is reclassified as a member of the same species.